2011
DOI: 10.1128/aem.02818-10
|View full text |Cite
|
Sign up to set email alerts
|

Acetogens and Acetoclastic Methanosarcinales Govern Methane Formation in Abandoned Coal Mines

Abstract: In abandoned coal mines, methanogenic archaea are responsible for the production of substantial amounts of methane. The present study aimed to directly unravel the active methanogens mediating methane release as well as active bacteria potentially involved in the trophic network. Therefore, the stable-isotope-labeled precursors of methane, [ 13 C]acetate and H 2 -13 CO 2 , were fed to liquid cultures from hard coal and mine timber from a coal mine in Germany. Guided by methane production rates, samples for DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Group 12 also contained abundant OTUs affiliated with acetogenic Acetobacterium, while associated production waters harbored methanogenic archaea affiliated with acetoclastic Methanosarcina. Indeed, the high abundance of potential acetogenic and methanogenic microbes agrees with previous reports implicating these taxa in syntrophic coal-to-methane transformations (41), where uncultured Rhodobacteraceae members identified here may play important roles in initial aromatic hydrocarbon degradation, as previously reported for representative isolates (42,43). Metagenome sequencing and binning.…”
Section: Resultssupporting
confidence: 77%
“…Group 12 also contained abundant OTUs affiliated with acetogenic Acetobacterium, while associated production waters harbored methanogenic archaea affiliated with acetoclastic Methanosarcina. Indeed, the high abundance of potential acetogenic and methanogenic microbes agrees with previous reports implicating these taxa in syntrophic coal-to-methane transformations (41), where uncultured Rhodobacteraceae members identified here may play important roles in initial aromatic hydrocarbon degradation, as previously reported for representative isolates (42,43). Metagenome sequencing and binning.…”
Section: Resultssupporting
confidence: 77%
“…The existence of a large number of Hydrogenophaga in coal and rock samples (Table 2) might be the reason why few hydrogenotrophic methanogens were detected at the Liulin site, given that members of Hydrogenophaga are typically described as being hydrogen-utilizing bacteria (Willems et al, 1989), and have been shown to be active in the enrichment of methanogenesis amended with coal using stable-isotope probing (SIP) (Beckmann et al, 2011). Fermentative bacteria inhabiting the CBM reservoir may be factors in the biodegradation of coal to fuel methanogens (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings greatly expand the known metabolic capabilities of Methanosaeta, which are abundant not only in anaerobic digesters, 19,20 but also in a diversity of methanogenic soils and sediments. [36][37][38][39] Methanosaeta is considered to produce more methane on Earth than any other methanogen, due to its ubiquitous distribution and its high affinity for acetate, the precursor of more than half of the methane in most methanogenic environments. 21 However, the energy yield from the conversion of acetate to methane is low (À75.7 kJ mol À1 methane) and the ability of Methanosaeta to also produce methane with electrons derived from DIET may add to their competitive advantage.…”
Section: Discussionmentioning
confidence: 99%